Duration of commodity funds operations in Poland and their effectiveness - Moskal, Agnieszka; Zawadzka, Danuta (Czas funkcjonowania funduszy surowcowych w Polsce a ich efektywność, 2019)
The effectiveness of investment results is one of the basic and most frequently analyzed issues related to investment funds. Research on factors affecting the effectiveness of funds in both foreign and Polish literature is rare. In the case of research on commodity funds, this is difficult due to the relatively young, still developing market. This study attempts to determine whether the duration of operation of commodity funds has an impact on the investment results obtained by them. To this end, the effectiveness of nine commodity funds operating on the Polish financial market in the period 2007-2018 was analyzed. As a measure of fund effectiveness, the rates of return and risk-adjusted measures were used: the Sharpe and Treynor ratios. The obtained results indicate that there is no clear relationship between the time of operation of commodity funds and the rates of return they receive
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 47-56